Analysis of The Use of Zoom Cloud Meeting Application in Integrated Science Learning During The Covid-19 Pandemic at Citra Bangsa Christian Junior High School - I Wayan Sukarjita; Maria Ina Tokan; Amiruddin Supu; Antonius Suban Hali (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2023)
The purpose of this research was to find out the analysis of the use of the zoom cloud meeting application in Integrated Science learning during the Covid-19 pandemic at Citra Bangsa Christian Middle School. The research method in this study uses qualitative research methods. The research subjects consisted of 5 Integrated Science teachers and 20 class VIIIH students at Citra Bangsa Christian Middle School. Data and data sources are in the form of primary data and secondary data. Data collection techniques in this study used the following research instruments: a) questionnaire (questionnaire), b) interviews, and c) documentation. Data analysis techniques in complete research use three activity flows simultaneously, namely; data reducation; presentation of data; conclusion. The data reducation part of the students' questionnaire answers was analyzed using a Likert scale, presenting the data in narrative text. The results of the research are that the Integrated Science learning process at the Middle School during Covid-19 using the zoom cloud meeting application generally went well, but the most common obstacle was network problems. The data in this research conclude that the use of the zoom cloud meeting application is an effective and practical learning medium used in the Integrated Science learning process at Citra Bangsa Christian Middle School during the Covid-19 pandemic.